Европейские ориентиры модернизации государственной службы в Украине - Юлия Лихач (ՀՀ ԳԱԱ հրատ.)
Հոդվածում քննության են առնվում քաղաքացիական ծառայության եվրոպական ստանդարտները և Ուկրաինայում դրանց ներդրման անհրաժեշտությունը: Վերլուծվում է քաղաքացիական ծառայության կանոնակարգմանը և կազմակերպմանը ցուցաբերված աջակցությունը: This article considers the European standards of Civil Service and the necessity of their implementation in Ukraine. The legal and organizational provision of Civil Service in Ukraine is as well considered. The primary issues that would support the development of Civil Service in Ukraine are emphasized.
Keywords: Political Science